Analisis Manajemen Pengelolaan Pesantren: Studi Kasus Manajemen Pesantren Al Khairot Malang - Hittotun Nahdiyah; Muhammad Husni (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the management of Pondok Pesantren Al-Khoirot (PPA) Malang in implementing an educational system that integrates traditional values with modern innovations. The method used is qualitative field research with subject determination techniques through purposive sampling and time sampling. Data collection was conducted through interviews, observation, and documentation, which were then analyzed using data reduction and data display. The results indicate that PPA Malang applies an integrated education system combining character education, religious knowledge, general sciences, and soft skills. The pesantren's management merges traditional (salaf) methods, such as the study of classic texts (kitab kuning) using